The relative importance of tax collection of gross salary income and wages in Algeria during the period 2016-2021: a case study of the wilaya of Skikda - Ahcene, Raki; Samir, Ammari (The journal of contemporary issues in business and government, 2022)
This study aimed to highlight and determine the role of the tax on the total income of salaries and wages in tax collection during the period 2016-2021: a case study of the wilaya of Skikda As this tax represents an important percentage of the total tax collection in Algeria, and due to the decline in tax collection revenues in recent years resulting from the repercussions of the “Corona” virus, Regarding the reduction of the rate of application of this tax by the state, there was a need to combine these data to get out of the cycle of crisis and improve tax collection The study concluded with a set of results, the most important of which was the high relative importance of the contribution of the tax on wages and salaries compared to other taxes during the years of study .and Its impact on the repercussions of the “Corona” virus was less severe than other types of taxes, and its contribution rates to regular collection increase compared to direct taxes.